Value, Economic Science and Historicity: an “archeological” approach . A preliminary approach: Um estudo preliminar - Herscovici, Alain (Geografares, 2020)
I intended to carry out an "archeology" of Economic Science  to highlight the different moments of construction of this Science. Within this perspective, I will study how, through the different paradigms present in Economic Science, the substantial hypothesis manifests itself; this hypothesis is based on the principle that economic goods, or commodities, have an intrinsic value. In the first part, I will study the main schools of thought, their relations and their internal contradictions. In a second part, I will highlight the elements that make it possible to understand what the autonomization of Economic Science consists of, and why the substantial hypothesis implicitly appears . In a third part, I will show how the substantial hypothesis manifests itself through the different theoretical matrices
Keywords: Historicity; Subtantial Hypothesis; Episteme